Pengaruh Beban Kerja Terhadap kinerja Karyawan F& B Services Departement di Intercontinentan Bali Resort - Thesa, Nila Lee; Kalpikawati, Ida Ayu; Sri Sadjuni, Ni Luh Gde (Program Studi Administrasi Perhotelan, 2025)
The intense competition in the hospitality industry demands high-quality service, with employee performance being a crucial factor influencing it. The purpose of this study is to determine the effect of workload on employee performance in the F&B service department at InterContinental Bali Resort. This research uses quantitative data and includes the entire population of 82 active employees as the sample. The analytical techniques used include validity tests, reliability tests, classical assumption tests, simple linear regression analysis, coefficient of determination tests, and t-tests. The results show that the workload variable has a positive and significant effect on employee performance, with a t-value (thitung) greater than the critical t-value (ttabel), specifically 9.721 > 1.664. The workload has a positive beta value of 0.676 on employee performance. Workload contributes to influencing employee performance by 54.2% in the moderate category, while the remaining 45.8% is influenced by other variables not examined in this study.